IMPLEMENTASI CONTROL OBJECTIVES FOR INFORMATION AND RELATED TECHNOLOGY TERHADAP AUDIT INTERNAL DI INDONESIA - Priyambodo, Stefani Rosaria (Jurnal Akuntansi AKUNESA, 2013)
Sistem control objectives for information and related technology is very advanced and has developed many advanced applied in countries such as Germany, Canada, United States of America, United Kingdom,etc. A lot of auditor use Control objective for information and Related Technology to understanding client?s company or organisation structure and internal control system, futhermore COBIT helps auditor to reveal about every single detail of it, such as their real expenses, benefit, deals and goals. This study aims to describe the system control objectives for information and related technology, as well as linkages with COBIT internal audit system. In addition, this study also aims to inform companies in Indonesia which are some who have implemented COBIT in their internal control systems. The result about this study is with the use of COBIT system in the company, it will be easier to achieve their goals as well as easier to avoid the possible risks that can be encountered. And for the auditor, COBIT greatly help facilitate auditor in view of the level of compliance, transparency, as well as the successful implementation of the system has been made. Key Words : Internal Audit, Control Objectives and Related Technology, IT Governance.